2002
DOI: 10.1055/s-2002-33236
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial High-Grade Neoplasia and Early Adenocarcinoma in Short-Segment Barrett’s Esophagus (SSBE): Curative Treatment Using Local Endoscopic Treatment Techniques

Abstract: The malignant potential of short-segment Barrett's esophagus must not be underestimated. Organ-preserving local endoscopic treatment shows good acute-phase and long-term results. Local endoscopic treatment represents an alternative to esophageal resection in the case of intraepithelial high-grade neoplasia and selected early adenocarcinomas in Barrett's esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(80 citation statements)
references
References 17 publications
1
71
0
8
Order By: Relevance
“…In a follow-up study of a total of 115 patients (EMR = 70, PDT = 32, APC = 3, EMR + PDT = 10) undergoing endoscopic treatment for HGD or EC, there was a 31% rate of metachronous or recurrent lesions over an average follow-up time of 34 ± 10 mo. Individually, the metachronous or recurrence rate was 30% (21/70) in the EMR group vs 37.5% in the EMR + PDT group [70] . It is important to note that the number of patients treated with the combined modality is markedly less than that treated with EMR alone.…”
Section: High-grade Dysplasia and Early Adenocarcinoma In Barrett's Ementioning
confidence: 91%
See 1 more Smart Citation
“…In a follow-up study of a total of 115 patients (EMR = 70, PDT = 32, APC = 3, EMR + PDT = 10) undergoing endoscopic treatment for HGD or EC, there was a 31% rate of metachronous or recurrent lesions over an average follow-up time of 34 ± 10 mo. Individually, the metachronous or recurrence rate was 30% (21/70) in the EMR group vs 37.5% in the EMR + PDT group [70] . It is important to note that the number of patients treated with the combined modality is markedly less than that treated with EMR alone.…”
Section: High-grade Dysplasia and Early Adenocarcinoma In Barrett's Ementioning
confidence: 91%
“…In fact, a recently-published multicenter, randomized controlled trial has shown that photodynamic therapy with Photofrin is superior than omeprazole alone in eliminating HGD at 5 years follow-up (77% vs 39%, respectively) [69] . To improve eradication of neoplastic tissue and decrease recurrence rates, the combined use of EMR with ablative techniques have been described [59,70] . Theoretically, recurrence rates are expected to be much lower with combined modalities, because both visible and non-visible lesions would be eradicated.…”
Section: High-grade Dysplasia and Early Adenocarcinoma In Barrett's Ementioning
confidence: 99%
“…EMR can be performed focally for staging endoscopically visible lesions that are suspicious for malignancy, but focal resection has been associated with a high rate of synchronous, metachronous and recurrent lesions in the residual Barrett's mucosa, which can reach to more than 30 % after a follow-up period of 3 years (92,111,(114)(115)(116). Therefore, once that all areas of localized neoplasia have been removed and appropriately staged, the remainder of the Barrett epithelium, in which there is a well established presence of molecular abnormalities, should be eradicated (5,117).…”
Section: Endoscopic Mucosal Resection (Emr)mentioning
confidence: 99%
“…In this capacity and either alone or in conjunction with other ablative techniques results appear quite favorable. 11,12,[39][40][41][42] Reports of extended resection of flat mucosa have been published; however, it is likely that such extensive therapy will require considerable expertise and not be routinely available in clinical practice.…”
Section: Therapy For Barrett's Esophagusmentioning
confidence: 99%